The systematics of the Hemiptera - FORERO, DIMITRI (Revista Colombiana de Entomología, 2008)
The Order Hemiptera comprises four main clades: Sternorrhyncha, Auchenorrhyncha, Coleorrhyncha and Heteroptera. In this article the main phylogenetic hypotheses for Hemiptera and its subgroups are reviewed. Important references regarding catalogs and identification aids are provided for the major groups, making emphasis in recent online tools.